Imaging how thermal capillary waves and anisotropic interfacial stiffness shape nanoparticle supracrystals - Zihao Ou (Nature Portfolio, 2020)
Interfacial fluctuations at the nanoscale, such as shape evolution of a growing crystal, are prohibitively difficult to study experimentally. Here, the authors are able to map the kinetic and thermodynamic parameters involved in shaping of nanoparticle supracrystals by directly imaging the fluctuating crystal surface by liquid-phase TEM, and analyzing it in the context of capillary wave theory.